Comparison of Clinical Profile between P. vivax and P. falciparum Malaria in Children: A Tertiary Care Centre Perspective from India. (9th April 2014) - Goyal, Jagdish Prasad; Makwana, Aarti M.
Abstract : Background. Malaria is a one of the leading causes of morbidity and mortality in tropical countries. Plasmodium vivax ( P. vivax ) is usually thought to be causing benign malaria with low incidence of complications as compared to Plasmodium falciparum ( P. falciparum ). Methods. This retrospective observational study included malaria patients who were admitted to K.T. Children Hospital and P.D.U. Government Medical College, Rajkot, a tertiary care teaching hospital, Gujarat, western India, during the period January 2012 to December 2012. Inclusion criteria were patients in whom either P. falciparum or P. vivax was positive on rapid malaria antigen test and peripheral blood smear. Patients showing mixed infections were excluded from study. Results. A total of 79 subjects (mean age 5.4 ± 3.6 years) were included in the study. It consisted of 47 P. vivax and 32 P. falciparum cases. The P. vivax cases consisted of 33 (70.2%) males and 11 (19.8%) females while P. falciparum cases consisted of 14 (43.8%) males and 18 (56.2%) females. One patient of each P. vivax and P. falciparum expired. There was no statistical significant difference found between complications such as anemia, thrombocytopenia, liver and renal dysfunction, ARDS, and cerebral malaria between P. vivax and P. falciparum . Conclusion. We conclude that P. vivax monoinfection tends to have as similar course and complications as compared to malaria due to P. falciparum monoinfection.